2013
DOI: 10.1371/journal.pntd.0002391
|View full text |Cite
|
Sign up to set email alerts
|

Differential Epidemiology of Salmonella Typhi and Paratyphi A in Kathmandu, Nepal: A Matched Case Control Investigation in a Highly Endemic Enteric Fever Setting

Abstract: BackgroundEnteric fever, a systemic infection caused by the bacteria Salmonella Typhi and Salmonella Paratyphi A, is endemic in Kathmandu, Nepal. Previous work identified proximity to poor quality water sources as a community-level risk for infection. Here, we sought to examine individual-level risk factors related to hygiene and sanitation to improve our understanding of the epidemiology of enteric fever in this setting.Methodology and principal findingsA matched case-control analysis was performed through en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
87
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 73 publications
(89 citation statements)
references
References 31 publications
1
87
1
Order By: Relevance
“…Consumption of food from street vendors has been found an independent risk factor for acquisition of paratyphoid fever in other Asian countries e.g. Nepal and Indonesia [13,14] . Of note, we observed also a two-fold increase of infections due to S. Typhi.…”
Section: Discussionmentioning
confidence: 99%
“…Consumption of food from street vendors has been found an independent risk factor for acquisition of paratyphoid fever in other Asian countries e.g. Nepal and Indonesia [13,14] . Of note, we observed also a two-fold increase of infections due to S. Typhi.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ongoing transmission of disease in endemic regions is likely to be driven largely by these recently-infected patients [40]. This scenario is supported by epidemiological studies that have shown disease transmission to close contacts within the household primarily from convalescent carriers rather than chronically infected individuals [13, 41]. Further, improved genetic analysis employing haplotyping of S. Typhi isolates and whole genome sequencing in highly endemic regions such as Vietnam and Nepal also found that acute typhoid is generally associated with a random distribution of organisms, rather than the same genotypes in close proximity [42].…”
Section: Epidemiology and Treatment Of Chronic Carriagementioning
confidence: 99%
“…In many developing countries, open defecation can lead to contamination of water systems, resulting in an increased risk of Salmonella transmission through the ingestion of bacteria in water used for drinking, washing, or irrigating produce [10][11][12]. Factors related to water source and storage, sanitation practices, and street food consumption have also been associated with increased risk of infection [13].…”
mentioning
confidence: 99%